OP38 Maintenance treatment with mirikizumab, a p19-directed IL-23 antibody: 52-week results in patients with moderately-to-severely active ulcerative colitis. (25th January 2019) - D'Haens, G Geert R; Sandborn, W J; Ferrante, M; Bhandari, B R; Berliba, E; Hibi, T; Tuttle, J; Canavan, J B; Friedrich, S; Durante, M; Arora, V; Feagan, B
Abstract: Background: Interleukin (IL)-23 is a critical cytokine in inflammatory bowel disease pathogenesis. Mirikizumab (miri), a p19-directed IL-23 antibody, demonstrated efficacy and was well-tolerated during 12 weeks of induction treatment in a Phase 2 randomised clinical trial (AMAC, NCT02589665). 1 Maintenance results through Week 52 from this trial are reported. Methods: Patients (Mayo score 6–12 with a minimum endoscopic subscore [ES] ≥2) were randomised 1:1:1:1 to receive intravenous (IV) placebo ( N = 63), miri 50 mg ( N = 63) or 200 mg ( N = 62) with possibility of exposure-based (EB) dose increases, or fixed miri 600 mg ( N = 61) every 4 weeks (Q4W), with efficacy assessment at Week 12. Patients who achieved a clinical response to miri at Week 12 were re-randomised 1:1 into a double-blind maintenance period to receive miri 200 mg subcutaneously (SC) Q4W ( N = 47) or every 12 weeks (Q12W; N = 46), and were treated through Week 52. See Table 1 for definitions of secondary and exploratory outcomes. Missing data were imputed as nonresponse. Results: Baseline (BL) characteristics of patients who entered the maintenance period were similar between groups. At BL, 52.7% had previously received a biologic. At Week 52, 46.8% (Q4W) and 37.0% (Q12W) were in clinical remission. Additionally, 80.9% (Q4W) and 76.1% (Q12W) had clinical response, and 57.4% (Q4W) and 47.8% (Q12W) had an ES = 0/1. Among those in clinical remission at Week 12, 61.1% (Q4W) and 38.5% (Q12W) remained in clinical remission at Week 52. Among those in clinical response (but not remission) at Week 12, 37.9% (Q4W) and 36.4% (Q12W) achieved clinical remission at Week 52. Symptomatic scores throughout the maintenance period are shown in Figure 1. During the maintenance period, 1 patient discontinued study due to an adverse event (AE), and similar frequencies of treatment-emergent AEs and serious AEs were reported across both treatment groups. Additional demographic, BL disease characteristics, and outcome data are reported in Table 1. Conclusions: Miri demonstrated durable efficacy (assessed by multiple measures) with no unexpected safety signals and few discontinuations due to AEs throughout the maintenance period. These are the first data demonstrating that a p19-directed IL-23 antibody may be an effective treatment as maintenance therapy in patients with moderately-to-severely active UC.